Non-Anatomic Approaches To Physical Education For Preschool Children (Journal of Pedagogical Inventions and Practices, 2025)
This article presents unconventional approaches to physical education classes for preschoolers, and focuses on the use of various movement games and a variety of exercises in classes for children aged 3-6